Greenhouse Gas Stabilisation: Principles to Guide the Formulation of Possible Targets and Policies and Measures (New Zealand Government, The Treasury, 1996)
The Ad Hoc Group on the Berlin Mandate at its fourth session requested the Secretariat to compile proposals relating to the treatment of quantified emission limitation and reduction objectives (QELROs) and policies and measures. This paper focuses on the principles for the development of new commitments. The paper does not attempt to cover all relevant issues and is not intended to be exclusive of other ideas.
Keywords: 330